Strategi Pengembangan UMKM Toko Kue Aminah di Kelurahan Oimbo melalui Digital Marketing dan Inovasi Produk - Ita Purnama; Sulistianingsih Sulistianingsih; Fitri Wulandari (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
MSMEs play a crucial role in the economy, yet many still struggle to adopt technology. This engagement aims to support the development of Toko Kue Aminah through digital marketing and product innovation. The activities were conducted through observation, interviews, and documentation during May 2025 in Oimbo Village. The results show that strategies such as utilizing Facebook and WhatsApp Business, adding product variations, and improving packaging and logo successfully enhanced the appeal and reach of the business. Furthermore, partnerships with local coffee shops have started to form, expanding product distribution. The synergy between digital marketing and product innovation has proven essential in boosting the business's competitiveness